A novel gellan–PVA nanofibrous scaffold for skin tissue regeneration: Fabrication and characterization. (20th January 2016) - Vashisth, Priya; Nikhil, Kumar; Roy, Partha; Pruthi, Parul A.; Singh, Rajesh P.; Pruthi, Vikas
Highlights: Electrospun gellan–PVA nanofibers (NFs) with uniform morphology were fabricated. PVA acted as supporting polymer and allowed the electrospinning of gellan solution. Skin tissue regeneration potential of fabricated nanofibers has been established. Abstract: In this investigation, we have introduced novel electrospun gellan based nanofibers as a hydrophilic scaffolding material for skin tissue regeneration. These nanofibers were fabricated using a blend mixture of gellan with polyvinyl alcohol (PVA). PVA reduced the repulsive force of resulting solution and lead to formation of uniform fibers with improved nanostructure. Field emission scanning electron microscopy (FESEM) confirmed the average diameter of nanofibers down to 50 nm. The infrared spectra (IR), differential scanning calorimetry (DSC) and X-ray diffraction (XRD) analysis evaluated the crosslinking, thermal stability and highly crystalline nature of gellan-PVA nanofibers, respectively. Furthermore, the cell culture studies using human dermal fibroblast (3T3L1) cells established that these gellan based nanofibrous scaffold could induce improved cell adhesion and enhanced cell growth than conventionally proposed gellan based hydrogels and dry films. Importantly, the nanofibrous scaffold are biodegradable and could be potentially used as a temporary substrate/or biomedical graft to induce skin tissue regeneration.